The Influence Of Sharia Financial Literacy And Financial Inclusion On Generation Z's Interest In Gold Investment With Inflation As A Moderating Variable (A Study At Pegadaian Syariah, Kediri District) - azkiyatul Mawazi; Safroni Isrososiawan; Nurul Susianti (IQTISHADUNA: Jurnal Ekonomi dan Keuangan Islam, 2026)
This study aims to analyze the influence of sharia financial literacy and sharia financial inclusion on gold investment interest among Generation Z at Pegadaian Syariah in Kediri District with inflation as a moderating variable. This study examines the partial and simultaneous effects of sharia financial literacy and sharia financial inclusion on gold investment interest, as well as the role of inflation in moderating these relationships. This research uses a quantitative approach with a correlational research design. Data were collected through questionnaires distributed to Generation Z respondents. The sample was determined using the Lemeshow formula because the exact population size was unknown. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial test (t-test), simultaneous test (F-test), and Moderated Regression Analysis (MRA). The results show that sharia financial literacy has no significant effect on gold investment interest, while sharia financial inclusion has a positive and significant effect on gold investment interest. Simultaneously, sharia financial literacy and sharia financial inclusion significantly influence gold investment interest. The moderation test indicates that inflation is able to moderate the relationship between sharia financial literacy and gold investment interest. This study emphasizes the importance of improving sharia financial literacy and financial inclusion to encourage gold investment interest among Generation Z, especially when considering macroeconomic factors such as inflation.